Implementasi Hipnoterapi Lima Jari terhadap Penurunan Kecemasan Pasien Kanker Serviks yang Menjalani Kemoterapi - Isran Isran; Tuti Nuraini; Yati Afiyanti; Agung Waluyo (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effect of five-finger hypnotherapy on cervical cancer patients undergoing chemotherapy. The method used is a systematic review of several databases such as Scopus, PubMed, ProQuest, and EBSCOHost to search for relevant articles. The results of the study show that a total of 10 pieces have been analyzed where there are several interventions in reducing anxiety in patients, one of which is using five-finger hypnotherapy, which has proven effective in reducing anxiety levels. In conclusion, giving a finger hypnotherapy intervention can reduce anxiety in cervical cancer patients before and after chemotherapy. Keywords: Five Finger Hypnotherapy, Cervical Cancer, Anxiety, Chemotherapy